Framework para gestão de riscos no transporte rodoviário de produtos perigosos para contribuir com a melhoria da mobilidade urbana - Pompone, Eduardo Cabrini (2017)
Urban areas growth stimulates consumption and, consequently, industrial production. As a result, as the chemicals are consumed by almost all industries, their distribution flow is increasing in cities. By their nature, these products pose risks to society and the environment. Therefore, the intensification of the flow increases the society's exposure to such risks. In this scenario, risk management in the transportation of dangerous products is a topic of academic, public management and managerial concern. The objective of this research is to propose a framework for risk management in the transportation of dangerous products to contribute to urban mobility improvement. The method adopted began with the bibliometric and systematic literature review for the identification of risk factors, mitigation measures and response actions in the transport of dangerous products. These elements made up the theoretical framework analyzed empirically in three case studies of accidents in the transport of dangerous products occurred in the Metropolitan Region of São Paulo from 2006 to 2016. Cases were selected due to the repercussions of the accidents, the occurrence of victims and the availability of respondents. Data collection of multiple cases occurred through documentary research, semi-structured interviews and direct observation. The results showed that there is no linear correspondence between risk, mitigation and response: the elements organize themselves in the form of a broad range of risk factors that converges to a smaller and central group of possible incidents, which, again, diverge for a wider range of consequences. In this structure, there are actions that can prevent the risk factors from triggering the incident (mitigation actions) or that the incident unfolds into consequences (response actions). If the unfolding occurs and reaches the environment, remediation actions of impacts (resilience plan) are also necessary. The structure described was well represented by the bow-tie type tool. It was shown that the tool is suitable for risk management in transporting dangerous products. In addition, it was possible to conclude that: (i) for each risk there is at least one associated mitigation; (ii) for each incident, there are different possible responses, depending, in this case, on the accident characteristics; (iii) for inefficient responses, unfolding consequences may occur, requiring resilience measures (iv) there are transversal mitigation actions, such as the training and collection of transport information, that have the potential to mitigate diverse risks; (v) elements in the Brazilian scenario of dangerous products transportation, that were not yet reported in the literature, should be considered in the framework, such as public safety risk (and associated mitigation actions "use of intelligent traffic lights", "improvement of public safety", "use of cargo escort") and financial compensation as a resilience plan action.